2016
DOI: 10.11648/j.edu.20160504.14
|View full text |Cite
|
Sign up to set email alerts
|

Students' Beliefs About Mathematics Learning and Problem Solving: The Case of Grade Eleven Students in West Arsi Zone, Ethiopia

Abstract: Abstract:Currently, there is a strong political focus in Ethiopia on science, engineering, and mathematics. This to be efficient and practical strong mathematics knowledge, which is built through effective mathematics learning and problem solving, is momentous. For this in turn students' beliefs about mathematics learning and problem solving play an important role; since students' beliefs are vital forces in students' mathematics learning and problem solving. Therefore, investigating students' beliefs about ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…Kemampuan belajar yang dibutuhkan seumur hidup oleh semua siswa dari segala usia adalah pemecahan masalah (Siniguian, 2017). Pemecahan masalah adalah proses ilmiah yang dilewatkan seseorang dari memahami masalah untuk menentukan informasi yang dibutuhkan untuk pemecahan masalah dan mengevaluasi kesesuaian solusi (Ayele, 2016;Ozturk & Guven, 2016). Kemampuan untuk memecahkan masalah dalam berbagai konteks pembelajaran sangat penting untuk pengembangan pengetahuan, pemahaman dan kinerja khususnya dalam pembelajaran matematika.…”
Section: Kemampuan Pemecahan Masalah Siswa Berdisposisi Matematis Rendahunclassified
“…Kemampuan belajar yang dibutuhkan seumur hidup oleh semua siswa dari segala usia adalah pemecahan masalah (Siniguian, 2017). Pemecahan masalah adalah proses ilmiah yang dilewatkan seseorang dari memahami masalah untuk menentukan informasi yang dibutuhkan untuk pemecahan masalah dan mengevaluasi kesesuaian solusi (Ayele, 2016;Ozturk & Guven, 2016). Kemampuan untuk memecahkan masalah dalam berbagai konteks pembelajaran sangat penting untuk pengembangan pengetahuan, pemahaman dan kinerja khususnya dalam pembelajaran matematika.…”
Section: Kemampuan Pemecahan Masalah Siswa Berdisposisi Matematis Rendahunclassified
“…In Ethiopia, studies that assess the mathematics self-efficacy of high school students are scarce, and the ones that are available (mainly student works) come up with contradictory findings. For example, the study by Abebe (2001) found gender differences favoring males, while the studies by Wubalem (2006) and Ayele and Dadi (2016) found no gender differences in students' mathematics self-efficacy. Contrary to these and many other findings described earlier, a study in Tigray, Ethiopia depicted that female grade 9 students have higher mathematics self-efficacy than their male counterparts (Tekola et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Melalui pembelajaran matematika berbasis pendekatan masalah, siswa akan lebih belajar mandiri untuk membangun pengetahuan tentang suatu konsep matematika, mengaitkan hubungan antar konsep, kemudian menggunakan konsep-konsep tersebut untuk menyelesaikan masalah non rutin yang ditemui. Dalam konteks ini, untuk membangun pengetahuan tentang konsep, fakta, prosedur, dan keterampilan dalam matematika, yang kuat, maka bisa dibangun secara efektif melalui pembelajaran matematika dan problem solving (Ayele & Dadi, 2016;Muhtarom, Juniati, Siswono, & Rahmatika, 2018).…”
Section: Membiasakan Pembelajaran Dengan Problem Solving (Pemecahan Munclassified